2022
DOI: 10.31788/rjc.2022.1516579
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Copper Oxide Nanoparticles Using Different Precursor

Abstract: Nano copper oxide (CuO) was synthesized using different precursors of copper salts such as copper acetate [Cu(CH3COO)2.2H2O] and copper chloride(CuCl2..2H2O) with the same experimental condition. The nanoparticles were characterized by UV-Vis, FT-IR, XRD, EDX, TEM, SAED, DLS and DSC. The results indicated that the grains of copper oxide were aggregated to formed particle sizes of about 50-100nm, 14.14-17.54nm and 283-449nm from TEM, XRD and DLS, respectively. The DLS analysis of CuONPs was also carried out in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The EDX spectrum of the lyophilized copper nanoparticle powder produced during the study showed that it contained about 91.93 % copper (Cu) and oxygen (O). Comparing our results to those published by Prasad and his team [ 26 ], assuming a copper acetate precursor, the atomic structures of copper (Cu) and oxygen (O) in the synthesized CuO-NPs were 53.21 % and 14.03 %, respectively. Cu's and O's atomic compositions were, when utilizing the copper chloride precursor, 57.78 % and 14.47 %, respectively.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The EDX spectrum of the lyophilized copper nanoparticle powder produced during the study showed that it contained about 91.93 % copper (Cu) and oxygen (O). Comparing our results to those published by Prasad and his team [ 26 ], assuming a copper acetate precursor, the atomic structures of copper (Cu) and oxygen (O) in the synthesized CuO-NPs were 53.21 % and 14.03 %, respectively. Cu's and O's atomic compositions were, when utilizing the copper chloride precursor, 57.78 % and 14.47 %, respectively.…”
Section: Discussionsupporting
confidence: 76%
“…In recent years, a range of nanoparticles have been produced using bacteria [ 26 ]. Their capacity to produce nanoparticles, such as copper oxide nanoparticles [ 26 ], is great.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This solid was collected, ground using a mortar and pestle, and annealed at 550 °C for 3 h. After being annealed, the product was ground again and stored in a glass vial at room temperature (RT) for further use. The same procedure was repeated using ammonium metavanadate to prepare the V 2 O 5 sample. , …”
Section: Methodsmentioning
confidence: 99%
“…The same procedure was repeated using ammonium metavanadate to prepare the V 2 O 5 sample. 29,30 Synthesis of CuO−V 2 O 5 Composite. In this procedure, the synthesized CuO and V 2 O 5 samples were taken in a 1:1 ratio and thoroughly mixed via gentle grinding using a mortar and pestle.…”
Section: ■ Introductionmentioning
confidence: 99%